Modelling the ecological patterns of a temperate lagoon in a very wet spring season - Lopes, J. F. (2010)
Phytoplankton blooms are very important events allowing the understanding of the coastal ecosystem dynamics, namely in situation of permanent or transient nutrient enrichment. The main objective of this paper is the study of the phytoplankton dynamics and the primary production rates along a strong gradient of salinity in a temperate lagoon, resulting from extreme weather conditions of a very wet spring season and corresponding to high river runoff and nutrient inputs. A 3D-ecological model consisted in a coupled physical and biological model based on the description of light-nutrients dependent phytoplankton and macroalgae growth, the phytoplankton production respiration and mortality, the nutrient cycling, as well as the zooplankton growth, was set up and applied to the Ria de Aveiro lagoon ecosystem in order to fulfil the purposes. The comparison between simulation and observation show that the model is a useful tool to understand the ecological status of the lagoon. On the other hand the model applications can be focused on local mechanisms controlling the main distribution of the biochemical variables in the lagoon as well as on the interaction between local conditions and the advective transport, induced by tides that influence the local balance and determine the bloom occurrence inside the lagoon. The modelling results show that during the study period the nutrient inputs from the freshwater tributaries support the uptake and growth of phytoplankton, reflecting high chlorophyll-a and dissolved oxygen concentrations as well as high values of the primary production. Their spatial distributions depend on local conditions and present a variability imposed by the lagoon characteristics and morphodynamics. The central areas and the far end areas, due to their shallowness and the proximity to the river boundaries, show the highest chlorophyll-a, primary production and dissolved oxygen concentration values, whereas those close to the lagoon mouth, where the influence of the transport and the dispersion by the tidal currents is dominant, show, in general, moderate values, unless a transport from the ocean boundary occurs.